Description of a new deep-water species of Alpheus Fabricius, 1798 from the Gulf of Mexico (Crustacea, Decapoda, Alpheidae) - Anker, Arthur; Nizinski, Martha (Zootaxa, 2011)
A new deep-water species of the snapping shrimp genus Alpheus Fabricius, 1798 is described from two offshore localities in the northern Gulf of Mexico, south of Louisiana. Alpheus lentiginosus n. sp. belongs to the A. macrocheles (Hailstone, 1835) species group and is most closely related to the western Atlantic A. pouang Christoffersen, 1979 and A. amblyonyx Chace 1972, the eastern Atlantic A. platydactylus Coutière, 1897 and A. macrocheles (Hailstone, 1835), and perhaps also to the eastern Pacific A. exilis Kim & Abele, 1988. The new species is associated with deep-water soft sediments adjacent to clusters of Lophelia pertusa (L.) (Scleractinia) or mud-covered rocks and cobble, at a depth range of 336–438 m, thus representing the deepest-known record of the Alpheidae in the Gulf of Mexico and the entire western Atlantic.